Investigating Arab/Muslim Character in Some Selected Post- Colonial Novels - Asst. Lecturer. Ahmad YasirDhain; Asst. Lecturer. Mugdad Abdul Imam Abood (Thi Qar Arts Journal, 2021)
Post- colonialism is a literary movement which is as an opposition to colonialism. Post-colonial literature is based on racial affairs (white and black) with its effects the society. It aims to investigate the reflection of the Arab/Muslim in post-colonial novels. This study hypothesizes that this type of the novels has the negative qualities of the Arab/Muslim character. This study falls into four sections. The first section is an introduction. The second section represents the reflection of the Arab character in Post-colonial literature. The third section deals with background information of post-colonial novels. The fourth section investigates the Arab/ Muslim character in some selected post –colonial novels . Finally, the study has reached some conclusions that verify the hypothesis of the study